Eficiencia de pseudomonas sp, rhodopseudomonas sp, micrococcus sp y bacillus sp empleados como cultivos individuales y en consorcio, en la degradación de petróleo diesel ii - Otiniano García, Nélida Milly Esther (2010)
In order to evaluate the efficiency of Pseudomonas sp, Rhodopseudomonas sp, Micrococcus sp, Bacillus sp, and the consortium formed by these four microorganisms in the diesel II petroleum degradation, it was worked in 5 bioreactors of aerated and shaken tank of 1.5 litters of capacity, with speed agitation of 120 rpm, and air flow of 0.5 vvm; in which were placed; 940 mL of Minimum Broth of Davies pH 7.0; 50 mL of diesel II petroleum as source of carbon and 10 mL of a suspension of approximately 3 x 107 bacteria /mL of the respective culture. The systems worked at 20 ± 2º C during 15 days. The petroleum degradation was evaluated determining: Percentage of total fats by the Method of Gerber; Biochemical Demand of Oxygen (BDO5), by the method of Winkler modified by Alsterberg and growth of biomass, by means of count in plate by incorporation. It was observed that the greater growth speed corresponds to Pseudomonas sp (2.36 day-1), microbial consortium (2.36 day-1), and Micrococcus sp (2.32 day-1) the statistic analysis Student- Neuman_Keuls (SNK) for multiple comparison of averages demonstrated that there is no significant difference between these microorganisms. As far as the speed of consumption of organic matter, expressed in DBO5, significant difference were observed in all the cases. When the speed of consumption of diesel II petroleum was determined, the majors percentage of efficiency corresponded to Pseudomonas sp (96,11%), followed by the consortium (94.83%) and Bacillus sp (89.32 %). It was concluded that when the microorganisms act in consortium the percentage of efficiency of diesel II petroleum degradation is major than the percentages of Bacillus sp, Rhodopseudomonas sp and Micrococcus sp, whereas the efficiency of Pseudomonas sp does not vary significantly when acting isolated or in consortium.